2017
DOI: 10.1186/s13059-017-1251-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic DNA methylation reconfiguration during seed development and germination

Abstract: BackgroundUnlike animals, plants can pause their life cycle as dormant seeds. In both plants and animals, DNA methylation is involved in the regulation of gene expression and genome integrity. In animals, reprogramming erases and re-establishes DNA methylation during development. However, knowledge of reprogramming or reconfiguration in plants has been limited to pollen and the central cell. To better understand epigenetic reconfiguration in the embryo, which forms the plant body, we compared time-series methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
205
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(236 citation statements)
references
References 48 publications
28
205
0
3
Order By: Relevance
“…DME can introduce single-strand nicks as part of a DNA demethylation pathway, whereas ROS1 represses homologydependent transcriptional silencing by demethylation of the target promoter (Gong et al, 2002). The importance of DNA methylation as an epigenetic marker required for several developmental phases such as seed development and germination was described recently (Kawakatsu et al, 2017). Several regions have been identified in which dynamic control of DNA methylation and transcriptional reactivation is contributing to reproductive development (Borges et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…DME can introduce single-strand nicks as part of a DNA demethylation pathway, whereas ROS1 represses homologydependent transcriptional silencing by demethylation of the target promoter (Gong et al, 2002). The importance of DNA methylation as an epigenetic marker required for several developmental phases such as seed development and germination was described recently (Kawakatsu et al, 2017). Several regions have been identified in which dynamic control of DNA methylation and transcriptional reactivation is contributing to reproductive development (Borges et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Together, these observations reveal that centromeric and pericentromeric repeats have a specific nucleosomal composition during early seedling development, with lower H3.1 occupancy in cotyledon nuclei early after germination compared to 5 dag. In agreement, data mining of recent transcriptomics data (Kawakatsu et al ., ) revealed low to undetectable transcript levels of most H3.1 ‐encoding genes in dry seeds and re‐expression during germination (Fig. S1b).…”
Section: Resultsmentioning
confidence: 99%
“…To explain the increase in H3.1 occupancy specifically at heterochromatin, we can envisage that after a genome‐wide incorporation during S‐phase, H3.1 is exchanged to H3.3 either in a transcription‐dependent manner at the genic regions analyzed here or globally in euchromatin as described previously during the transition from cell proliferation to differentiation in the root (Otero et al ., ). Interestingly, most H3.1‐encoding genes are not expressed in the dry seed (Kawakatsu et al ., ; Narsai et al ., ), in agreement with absence of replicative activity (Barroco et al ., ) pointing towards a peculiar H3.1 : H3.3 balance in the dry seed that might favor chromatin decondensation during germination. Furthermore, the resumption of replication activity after germination renders this developmental time window particularly suitable to decipher changes in chromatin and nuclear organization linked to DNA replication coupled histone deposition.…”
Section: Discussionmentioning
confidence: 98%
“…Wild-type sperm has low CHH methylation (Calarco et al, 2012), indicating that the paternal genome must gain methylation after fertilization. Recent studies from soybean and Arabidopsis have shown that CHH methylation increases during embryogenesis (Kawakatsu et al, 2017;Lin et al, 2017;Narsai et al, 2017). In mature Arabidopsis embryos, CHH methylation approaches 100% at individual cytosines, whereas in other tissues, including younger embryos, individual CHH sites are c. 20% methylated (Bouyer et al, 2017).…”
Section: Heritability and Reinforcement Of Dna Methylation In The mentioning
confidence: 99%
“…In mature Arabidopsis embryos, CHH methylation approaches 100% at individual cytosines, whereas in other tissues, including younger embryos, individual CHH sites are c. 20% methylated (Bouyer et al, 2017). Methylation decreases upon seed germination, likely through a passive mechanism (Bouyer et al, 2017;Kawakatsu et al, 2017;Lin et al, 2017;Narsai et al, 2017). It is unknown whether the increased CHH methylation in developing embryos is functional: mutation of the de novo methyltransferases DRM2 and CMT2 prevents CHH methylation but without obvious effects on seed development or germination, although it is unclear how comprehensively phenotypes have been assessed.…”
Section: Heritability and Reinforcement Of Dna Methylation In The mentioning
confidence: 99%